Book Review: V. Ratten (edited by), Covid-19 and entrepreneurship, challenges and opportunities for small business, Routledge, 2021 - Chamochumbi Diaz, Gail Denisse (Piccola Impresa / Small Business, 2024)
The book is one of the first attempts to examine the links between the Covid-19 pandemic and entrepreneurship by focusing on small businesses. Taking a holistic approach, the authors suggest different strategies that firms might adopt to meet the challenges and seize the opportunities presented by the crisis. Another issue that the authors tackle is how institutional structures and policies can either promote or impede growth. It is a timely multidisciplinary analysis which offers entrepreneurs, practitioners, and policy makers considerable food for thought as to what ‘doing business’ means in an uncertain environment.